Ataque de las polillas Scrobipalpopsis solanivora y phthorimaea operculella (Lepidoptera, Gelechiidae) y su relación con la fenología de la papa en Cartago, Costa Rica. (ING) - Hilje, Luko (1989)
Growth of vegetative structures (foliage, tubers and roots) and flowering patterns were studied for Atzimba and “Segura” potato varieties. Leaf number increased linearly and plant height followed a sigmoid pattern during the growing season; fresh and dry weights of vegetative parts increased in a curvilinear manner. The largest absolute production of aerial biomass occurred between the 5th and 7th weeks, and that of tubers occurred between the 13th and 15th weeks. Flowering and tuberization began at the 6th week. Tubermoths appeared on potato fields at flowering onset. Thus, the hypothesis the Tubermoths are attracted by the flowers is proposed. A phenological crop model is presented, based on which options to diminish tubermoth economic impact are discussed.